2012
DOI: 10.1167/iovs.12-10892
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Relationship between FDF, FDT, SAP, and Scanning Laser Ophthalmoscopy in Glaucoma Patients

Abstract: The correlation between structure and function is stronger in FDF and FDT compared with SAP. Correlations are strongest in temporal areas where glaucomatous damage tends to occur first. A better understanding of the structure-function relationship should allow for improved detection and management of glaucoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 40 publications
2
35
1
Order By: Relevance
“…Previous studies have also demonstrated that poor agreement between structures using confocal scanning laser ophthalmoscopy (cSLO) and HFA progression was observed at various stages of the disease. 40,42,53,54 Strouthidis et al have shown that in subjects with ocular hypertension, 21.2% progressed by cSLO criteria alone and 20.2% by SAP alone, and 12.1% progressed by both cSLO and SAP when examined prospectively over 7 years. 42 These cross-sectional studies suggest that some eyes progress in VF before they progress in the imaging devices, and there may be a disconnection between structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also demonstrated that poor agreement between structures using confocal scanning laser ophthalmoscopy (cSLO) and HFA progression was observed at various stages of the disease. 40,42,53,54 Strouthidis et al have shown that in subjects with ocular hypertension, 21.2% progressed by cSLO criteria alone and 20.2% by SAP alone, and 12.1% progressed by both cSLO and SAP when examined prospectively over 7 years. 42 These cross-sectional studies suggest that some eyes progress in VF before they progress in the imaging devices, and there may be a disconnection between structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…Lamparter et al compared the results from SAP, FDF perimetry, FDT perimetry and laser ophthalmoscopy [14]. In their study the Humphrey perimeter was a SAP, FDT perimetry used the Humphrey Matrix-FDT, while the FDF perimeter used HEP.…”
Section: Discussionmentioning
confidence: 99%
“…It stimulates M cells of the retina, which constitute 4% of the retinal population of ganglion cells. M cells, with M y subtype, are very sensitive to damage as a result of glaucoma and are damaged during an early stage of the disease [10,14]. Even a small loss of the large ganglion cells influences visual functions and, as a result, this type of visual field.…”
mentioning
confidence: 99%
“…The FDF stimulus has recently been proposed as an alternative method for detecting glaucomatous visual loss (Horn et al, 2014;Lamparter et al, 2012;Marvasti et al, 2013). The Heidelberg edge perimeter (HEP) uses the FDF stimulus to measure local contrast sensitivities at 54 test locations equivalent to test points on SAP 24-2.…”
Section: Figurementioning
confidence: 99%
“…Recent studies have examined the ability of FDF perimetry to detect glaucoma (Liu et al, 2014a,b) and compared it to Matrix FDT and SAP (Horn et al, 2014;Lamparter et al, 2012). It was reported that abnormalities on FDF were frequently present in eyes with glaucomatous structural changes but normal SAP.…”
Section: Figurementioning
confidence: 99%